2014
DOI: 10.18632/oncotarget.1816
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the anaphase-promoting complex/cyclosome (APC/C)- bromodomain containing 7 (BRD7) pathway for human osteosarcoma

Abstract: Osteosarcoma is the most common primary malignant bone tumor in childhood and adolescence and has a propensity for local invasion and early lung metastasis. However, the current therapies often result in chemoresistance, and a therapeutic target is not available in the clinic for osteosarcoma. Here, we report that BRD7 forms a complex with the anaphase-promoting complex/cyclosome (APC/C) and is degraded by APC/Ccdh1 and APC/Ccdc20 during the cell cycle. Moreover, BRD7 is a tumor suppressor in osteosarcoma, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…Accumulating evidence demonstrates that inactivation of the BRD7 gene contributes to the development of many human cancers by transcriptional dysregulation [1,2,[6][7][8][9][10][11][12][13]. BRD7 regulates signaling pathways that involve cell growth, apoptosis, cell cycle, and mobility [14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence demonstrates that inactivation of the BRD7 gene contributes to the development of many human cancers by transcriptional dysregulation [1,2,[6][7][8][9][10][11][12][13]. BRD7 regulates signaling pathways that involve cell growth, apoptosis, cell cycle, and mobility [14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that BRD7 was also down-regulated in multiple types of human cancer, including breast [6], prostate [7], endometrial [8], colorectal [9], ovarian [10], and pancreas cancer [11], glioma [12], and osteosarcoma [13]. BRD7 can inhibit cell growth through multiple mechanisms, including cell cycle arrest and apoptosis [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found to inhibit the cell cycle G1-S phase progression, initiate apoptosis and reverse cellular malignancy through the ras/MEK/ERK, Rb/E2F and Wnt signaling pathways. [1][2][3][4] BRD7 is a member of the bromodomain family, which includes BRD2, BRD3, BRD9 and BRDT, [5][6][7] and can recognize and bind to acetylated histone H3. 8 BRD7 is primarily localized in the nucleus and possesses a functional nuclear localization signal sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Using the bioinformatics tool (Targetscan), we demonstrated that miR‐410 bound to the 3′‐UTR of BRD7. BRD7 is downregulated in various malignancies, which encourage us to believe that BRD7 may be a miR‐410 direct target in NSCLC [39–41]. In addition, miR‐410 inhibited BRD7 mRNA and protein expression.…”
Section: Discussionmentioning
confidence: 97%